PENGARUH PEMBIAYAAN MURABAHAH DAN MARGIN MURABAHAH TERHADAP RETURN ON ASSET BANK UMUM SYARIAH DI INDONESIA - Tabrani, Tabrani (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2022)
This study aims to analyze the effect of financing on the profitability of Islamic commercial banks as proxied by the ROA ratio for the 2017-2021 period, and analyze the magnitude of the contribution of financing to the ROA of Islamic commercial banks. The analysis technique used in this research is descriptive quantitative and simple linear regression. The results show that financing has a positive effect on ROA of Islamic commercial banks. The contribution of financing to the ROA of Islamic commercial banks is 59.4%. Murabahah receivables provide the largest contribution to the ROA of Islamic commercial banks compared to mudharabah financing, musyarakah financing, ijarah financing, qard receivables, and istishna receivables.